2014
DOI: 10.1039/c4nj00700j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-scaffolded amphiphilic aminoglucoside clusters: self-assembling and gene delivery capabilities

Abstract: Precise control over the architecture of gene carriers is instrumental to manipulate gene delivery efficiency.Combining cationic centers and carbohydrate motifs into monodisperse architectures has been proposed as a suitable strategy to impart nucleic acid condensation abilities while preserving biocompatibility. Herein, we have assessed the influence of the arrangement and orientation of cationic elements on the self-assembling and gene transfer capabilities of polycationic glycoamphiphilic cyclodextrins (pGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…[24,25] Almost all reporteds upramolecular gene-delivery systems that exploit CD-inclusion capabilities are engineered from mac-romolecules bearing complementary host and guest moieties [26,27] or from small-molecule CD derivatives and macromolecular partners [28][29][30] in which at least one of the components has ap olycationic nature.T he combinationo fs everal elemental noncovalenti nteractions results in hierarchically ordered materials that can further condense nucleic acidsa nd mediate transfection.Although the flexibilityo ft he self-assembling process, its dynamic nature,a nd the facile optimization of supramolecular polycations bear some advantages relative to covalent polycations, the intrinsic polydisperse nature and random conformation of the macromolecular components represents al imitation for studies into structure-activity relationshipsa nd batch-to-batchr eproducibility.T he development of small-molecule-based supramolecular vectors for gene therapy has thus become an urgent need. To date, three different CD-based approaches have been proposed toward this goal: 1) linear redox-sensitive supramolecular polymers assembled from ad itopic b-CD host and ad itopic polycationic bisferrocene guest; [31] 2) multihead-multitail polycationic amphiphilic CDs (paCDs), which assemble in the presence of pDNA to form onionlike nanocomplexes (CDplexes) with alternating paCD bilayers and polynucleotide chains, although disordered in aqueous solution; [32][33][34][35][36][37] and 3) xylylene-capped CD-centered polycationic clusters that form dimers in aqueous media, which can bridge DNA fragments in ap H-dependent reversible manner [38] ( Figure 1). In spite of considerable success, the above approaches suffer from either low control over the elementary supramolecular speciesorr elativelyh igh synthetic cost, whichhamper further development.W ec onceivedt hat such drawbacks could be mitigated by using simple CD-centered polycationic clusters throught he implementationo fa na dditional level of self-assembly promoted by ditopic hosts.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Almost all reporteds upramolecular gene-delivery systems that exploit CD-inclusion capabilities are engineered from mac-romolecules bearing complementary host and guest moieties [26,27] or from small-molecule CD derivatives and macromolecular partners [28][29][30] in which at least one of the components has ap olycationic nature.T he combinationo fs everal elemental noncovalenti nteractions results in hierarchically ordered materials that can further condense nucleic acidsa nd mediate transfection.Although the flexibilityo ft he self-assembling process, its dynamic nature,a nd the facile optimization of supramolecular polycations bear some advantages relative to covalent polycations, the intrinsic polydisperse nature and random conformation of the macromolecular components represents al imitation for studies into structure-activity relationshipsa nd batch-to-batchr eproducibility.T he development of small-molecule-based supramolecular vectors for gene therapy has thus become an urgent need. To date, three different CD-based approaches have been proposed toward this goal: 1) linear redox-sensitive supramolecular polymers assembled from ad itopic b-CD host and ad itopic polycationic bisferrocene guest; [31] 2) multihead-multitail polycationic amphiphilic CDs (paCDs), which assemble in the presence of pDNA to form onionlike nanocomplexes (CDplexes) with alternating paCD bilayers and polynucleotide chains, although disordered in aqueous solution; [32][33][34][35][36][37] and 3) xylylene-capped CD-centered polycationic clusters that form dimers in aqueous media, which can bridge DNA fragments in ap H-dependent reversible manner [38] ( Figure 1). In spite of considerable success, the above approaches suffer from either low control over the elementary supramolecular speciesorr elativelyh igh synthetic cost, whichhamper further development.W ec onceivedt hat such drawbacks could be mitigated by using simple CD-centered polycationic clusters throught he implementationo fa na dditional level of self-assembly promoted by ditopic hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, the 6-amino-6-deoxyglucoside pGaCD was found to selectively bind the galactose-specific lectin peanut agglutinine (PNA) and preferentially internalize BNL-CL2 hepatocytes by ASGPR-mediated endocytosis [171], highlighting this iminosugar as a dual nucleic acid/lectin receptor binder when presented in multivalent form (Figure 17). Jiménez Blanco, Di Giorgio and coworkers proposed an alternative pGaCD vector design that displayed aminoglucosyl units attached at all primary positions of the per(O-2,O-3)-hexanoylated βCD scaffold, instead of bearing amine groups and sugar ligands at separate branches [170]. They encountered that the self-assembling and transfection aptitude of these compounds were very sensitive to the aminoglycoside structure: 6-amino-6-deoxy and 2-amino-2-deoxy-β-Dglucopyranosylthioureido conjugates readily formed glycoCDplexes (75-100 nm hydrodynamic diameter) in the presence of pDNA, but only the first ones were efficient at promoting transfection in COS-7 cells.…”
Section: Biomacromolecule-templated Formation Of Functional Glycocd Nmentioning
confidence: 99%
“…The increase in efficiency at delivering the cargo to target cells was ascribed to an enhanced endosomal escaping ability through the cooperative action of a proton sponge effect of PAMAM dendrimer and the inclusion ability of αCD towards phospholipids in Figure 17. Structure of the 6-amino-6-deoxy β-D-glucopyranosylthioureido/βCD conjugate prepared by Jiménez Blanco, Di Giorgio and coworkers, and an illustration of their co-assembly with pDNA to form nanocomplexes that promoted ASGPR-mediated transfection of hepatocytes [170,171]. A representative TEM micrograph of the nanocomplexes is also shown.…”
Section: Biomacromolecule-templated Formation Of Functional Glycocd Nmentioning
confidence: 99%
“…In 2012, the same research group reported amphiphilic CDs derivatized with aminoglucoside 50-52 or with galactosyl motifs 53 - 54 74, 75. Compounds 50 and 52 can efficiently promote cellular uptake and subsequent gene expression in COS-7 cells.…”
Section: Amphiphilic Cds For Gene Deliverymentioning
confidence: 99%